2012
DOI: 10.1177/2150135111426298
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Perioperative Near-Infrared Spectroscopy During Neonatal and Infant Congenital Heart Surgery for Adverse In-Hospital Clinical Events

Abstract: At bypass conclusion, 10 minutes of MUF does not adversely affect cerebral or renal NIRS. Left and right cerebral NIRS are equal, so that biparietal cerebral NIRS monitoring is probably not warranted. Perioperative cerebral and renal NIRS readings, respectively, below 45% and 40% correlate with ECMO/death and renal NIRS below 30% with prolonged ICU stay. Cerebral NIRS and lactate levels showed a strong inverse correlation during the first six postoperative hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“…Nevertheless, CPB is affected by significant morbidity due to several factors, including extent and duration of blood contact with CPB circuit, hemodilution, and changes in perfusion temperature. Several studies have shown efficacy of cerebral and renal rSO2 in detecting low cardiac output state both during CPB and during intensive care unit (ICU) stay (3,4). Strategies aimed at mitigating SIRS include management of perfusion temperature toward mild hypothermia or normothermia, reduction of hemodilution, circuit miniaturization, and biocompatibility improvement (2).…”
mentioning
confidence: 99%
“…Nevertheless, CPB is affected by significant morbidity due to several factors, including extent and duration of blood contact with CPB circuit, hemodilution, and changes in perfusion temperature. Several studies have shown efficacy of cerebral and renal rSO2 in detecting low cardiac output state both during CPB and during intensive care unit (ICU) stay (3,4). Strategies aimed at mitigating SIRS include management of perfusion temperature toward mild hypothermia or normothermia, reduction of hemodilution, circuit miniaturization, and biocompatibility improvement (2).…”
mentioning
confidence: 99%
“…Although the cited literature varies widely in range for ACP from 10 to 100 mL/kg/min, studies utilizing NIRS technology or visual light spectroscopy have indicated that ACP flow rates of greater than 30 mL/kg/min are sufficient to maintain adequate cerebral and somatic oxygen saturations (12,19,40). Admittedly, these findings must be evaluated within the context of temperature and blood gas management (pH versus alpha stat) among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic ischemia is theoretically lessened during arch reconstruction and the risks of neurological and cognitive deficits following operation are presumably reduced (8,9). With increased experience with ACP in the field of adult aortic arch reconstruction, a more recent evolution from deep hypothermia toward the use of warmer temperatures has occurred (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the application of somatic rSO 2 provides an indicator for renal or lower body perfusion. A cerebral NIRS value below 45% and a renal NIRS value below 40% has a strong correlation with the incidence of ECMO or hospital death and a renal NIRS below 30% correlated with prolonged ICU stay (49,50). This information coupled with standard blood gas and lactate analysis provides a basic picture of perfusion adequacy.…”
Section: Physical Parameter Measurements and Data Capturementioning
confidence: 99%